#### Answer

x=6

#### Work Step by Step

Simplifying
7x + 9 = 9x + -3
Reorder the terms:
9 + 7x = 9x + -3
Reorder the terms:
9 + 7x = -3 + 9x
Solving
9 + 7x = -3 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
9 + 7x + -9x = -3 + 9x + -9x
Combine like terms: 7x + -9x = -2x
9 + -2x = -3 + 9x + -9x
Combine like terms: 9x + -9x = 0
9 + -2x = -3 + 0
9 + -2x = -3
Add '-9' to each side of the equation.
9 + -9 + -2x = -3 + -9
Combine like terms: 9 + -9 = 0
0 + -2x = -3 + -9
-2x = -3 + -9
Combine like terms: -3 + -9 = -12
-2x = -12
Divide each side by '-2'.
x = 6
Simplifying
x = 6